2019
DOI: 10.30591/siklus.v8i1.1210
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Predisposisi Sebagai Penentu Pemanfaatan Pos Pembinaan Terpadu Penyakit Tidak Menular

Abstract: Non-infectious disease is one of the major causes of death in the world. Non-infectious disease prevention efforts in Indonesia are carried out through Integrated Service Post. The implementation of integrated service post of non-infectious disease in Mojolaban still encounters various problems. One of them is low utilization of integrated service post of non-infectious disease. This research was aimed at analyzing predisposition factors as determinant of integrated service post utilization of non-infectious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…This study is in line with Nasution and Hutabarat (2018) research on the Effect of Predisposition, Enabling, and Reinforcing on the Utility of Integrated NCDs Posyandu (Sig-p = 0.000 < 0.001 PR 3.306), which showed that respondents' attitudes were negative 3,306 times. This research is also in line with the 􀅫indings of Sugiarsi et al (2019), Predisposing Factors as Determinants of Posyandu Use for NCDs. In the working area of the Mojolaban Health Center, previous studies revealed a relationship between attitudes and consumption of PTM Posbindu (Sig-p = 0.032 OR 5.542), which was supported by this study.…”
Section: The In􀅮luence Of Attitudes With the Use Of Ptm Posbindu In T...supporting
confidence: 87%
See 1 more Smart Citation
“…This study is in line with Nasution and Hutabarat (2018) research on the Effect of Predisposition, Enabling, and Reinforcing on the Utility of Integrated NCDs Posyandu (Sig-p = 0.000 < 0.001 PR 3.306), which showed that respondents' attitudes were negative 3,306 times. This research is also in line with the 􀅫indings of Sugiarsi et al (2019), Predisposing Factors as Determinants of Posyandu Use for NCDs. In the working area of the Mojolaban Health Center, previous studies revealed a relationship between attitudes and consumption of PTM Posbindu (Sig-p = 0.032 OR 5.542), which was supported by this study.…”
Section: The In􀅮luence Of Attitudes With the Use Of Ptm Posbindu In T...supporting
confidence: 87%
“…(2018). In line with that, research conducted by Sugiarsi, Wigunantiningsih, and Kusumawati (2019) found that the utilisation of PTM POSBINDU was in􀅫luenced by knowledge (p = 0.036) OR = 4.789 and attitude (p = 0.032) OR = 5.542. In a different study conducted by Anggraeni and Fauziah (2020), the results showed that the combination of the use of POSBINDU PTM was signi􀅫icant (p = 0.000), and variables of knowledge and attitudes drove this, and family support with an R-value of 0.580 squared.…”
Section: Introductionsupporting
confidence: 68%